Análisis estadístico en la planificación de la demanda del proceso denominado COPACKING en una industria de fabricación masiva de alimentos - Medina Cevallos, Nicolás Francisco (2018)
The present degree work consists of a proposal for improvement in the process called COPACKING in an industry of mass consumption of food, where it seeks to reduce the costs involved in the planning of demand. For the analysis of the real state, the historical information of the demand and the budget was analyzed, where very relevant information regarding the historical behavior of the demand of 11 packages was obtained. Throughout the analysis, you can identify the problem from which a root cause is derived, which is solved through the proposed change of the forecast generation method. The proposed solution consists in changing the method of generation of forecasts for each case by applying methods of analysis of the time series against the statistical error of a period of 3 months. Finally, due to the application of the improvement proposal, which allows us to attack the root cause found, it is possible to demonstrate that if it uses the proposed methods, the company would have generated 64132 dollars more than what it generated in the period analyzed.